DIELECTRIC PROPERTIES NEMATIC LIQUID CRYSTAL WITH A LOW CONTENT OF Au NANOPARTICLES - Ковальчук, О.; Костенчук, Н.; Семенко, С. (Science-based technologies, 2011)
Using the method oscilloscope we have studied the influence of gold nanoparticles of 3–5 nm in diameter and with the maximum concentration of 0.1 wt. % on dielectric properties of the planar oriented nematic liquid crystal 6CHBT. It was shown that the nanoparticles changed significantly the parameters of near-electrode areas (almost by one order of magnitude) and conductance (about 4 times). These changes non-linearly depended on the concentration of nanoparticles.